Ecology of the hyperoceanic liverwort Leptoscyphus cuneifolius (Hook.) Mitt. at a key site in the British Isles. (2nd April 2020) - Callaghan, Des A.
ABSTRACT: Introduction . Leptoscyphus cuneifolius has a very limited distribution in Europe and is threatened with extinction in several regions. This study investigates its ecology at Coed y Rhygen, the most important site in Wales. Methods . GPS-based surveys documented the distribution of L. cuneifolius within the study site. Hillshade analysis was used to investigate preference for topographic locations in relation to solar illumination. Thirty relevés were recorded to describe habitat conditions and community composition. Four monitoring plots for L. cuneifolius, first recorded in 1997, were re-visited. Results . A total of 309 locations of L. cuneifolius was recorded, distributed across 226 10 m grid cells. Hillshade analysis showed a preference for shaded topography. The liverwort comprised only sterile material at all locations and occurred almost exclusively on the trunks of trees. Results from relevés show a marked preference for micro-habitats with a northerly aspect. The most common associates are the liverworts Frullania tamarisci and Plagiochila punctata . Trend in abundance of four monitored colonies of L. cuneifolius during 1997–2019 shows a decline at all locations, including extinction at two. Conclusions . Within the study area, L. cuneifolius prefers shaded locations at both macro- and micro-habitat scales, and is almost exclusively an epiphyte, with a clear preference for the acidic bark of Betula pubescens . It is entirely dependent on asexual reproduction, via tiny caducous leaves, produced abundantly. The tiny size of L. cuneifolius makes it particularly vulnerable to competitive exclusion from habitat patches, not only due to over-growth by larger bryophytes, but also mucilaginous algae.